A Global Outlook on Sustainable Plant Acquisition: A Review of Scholarly Works - Sulistyowati, Tussi; Husda, Nur Elfi (International Journal of Multidisciplinary Approach Research and Science, 2023)
In today's horticultural landscape, plant acquisition is under scrutiny due to sustainability concerns and the desire to enhance the consumer experience. This study employs a qualitative literature review methodology spanning 2019 to 2023, using the Scopus database and Harzing's Publish or Perish tool to ensure article relevance and timeliness. Employing keywords like "plant buying," "plant purchase," "plant shop," "buying plant," "plant shopping," "plant procurement," and "purchasing plants," the search yielded 42 articles, with 10 selected for their relevance, reputable sources, and empirical or theoretical contributions. This research explores two key aspects: the variation in plant purchasing behaviors among different countries and the role of technology in shaping plant acquisition in the digital era. Across nations, disparities in plant purchasing behaviors emerge, shaped by cultural norms, economic conditions, and technological advancements. Technological innovations like garden design apps, QR codes, and cloud-based solutions streamline the plant acquisition process, enhancing garden planning, information accessibility, and supply chain management, promoting efficiency and sustainability in horticulture.